The Effect of Product Quality, Digital Marketing, and Brand Image on Purchase Decisions at Cubic Art Bali - Anak Agung Putri Saraswati; I Gusti Ngurah Agung Gede Eka Teja Kusuma; Ni Putu Nita Anggraini (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
This study aims to analyze the influence of product quality, digital marketing, and brand image on purchasing decisions at Cubic Art Bali. The phenomenon of increasing competition in the arts and crafts industry requires companies to strengthen product quality, digital marketing strategies, and brand image in order to enhance consumer purchasing decisions. The research design employed is quantitative research using an associative approach. The population in this study consists of Cubic Art Bali consumers, while the sample consists of 144 respondents obtained through a non-probability sampling technique, namely incidental sampling. Data collection was conducted by distributing questionnaires. The data analysis techniques used include Validity and Reliability Tests, Classical Assumption Tests, Multiple Linear Regression Analysis, as well as t-tests and F-tests. The results of the study indicate that: (1) product quality has a positive and significant influence on purchase decisions; (2) digital marketing has a positive and significant influence on purchase decisions; and (3) brand image has a positive and significant influence on purchase decisions. These findings suggest that the higher the product quality, the more effective the digital marketing strategy, and the more positive the brand image, the higher the purchase decisions of consumers at Cubic Art Bali.